Analisis Kinerja Keuangan Pemerintah Daerah Dalam Pengelolaan Anggaran Pendapatan Dan Belanja Daerah Di Kabupaten Temanggung Tahun 2020-2022 - Ivo Vianita; Sevin Nurlaila Rahmawati; Ana Aulia (STIKes Ibnu Sina Ajibarang, 2024)
This research was conducted to determine the Financial Performance of Temanggung Regional Revenue and Expenditure for the 2020-2022 Fiscal Year. Analysis of the Budget Realization Report using the independence ratio, effectiveness ratio and efficiency ratio can determine the Financial Performance of Income and Expenditures. This research uses a qualitative descriptive method, specifically using the Temanggung Regional Budget Realization Report (LRA) for 2020-2022. The results of this research show that the Financial Performance of Temanggung Regional Income and Expenditures in 2020 to 2022 is not yet independent because seen from the independence ratio it still shows regional dependence on government assistance. In 2020 and 2021 it can be said to be effective and quite efficient. Meanwhile, in 2022, the Financial Performance of Temanggung Regional Revenue and Expenditures experienced a decline in performance, resulting in less effective performance and quite efficient spending. From the results of the research carried out, it is hoped that the Temanggung regional government will be able to carry out evaluations by paying attention to the level of independence, efficiency and effectiveness ratios in order to advance the future.